Mycotoxicological and palynological profiles of commercial brands of dried bee pollen - Deveza,Michele Valadares (2015)
Abstract Pollen is used in the human diet as a food supplement because of its high nutritional value; however, this product is prone to fungal contamination that could potentially generate toxins that are harmful to human health. This study aimed to verify the floral diversity of commercial brands of bee pollen and their mycotoxicological safety for human consumption. A total of 27 bee pollen samples were analyzed; these samples represented commercial brands, either showing an inspection seal or not, marketed in the State of Rio de Janeiro. The analyzed parameters included floral diversity through palynological analysis, water activity, fungal counts, identification and toxigenic profiles. The palynological analysis identified nine plant families, of which the Asteraceae was predominant. Analysis of hygienic quality based on fungal load showed that 92% of samples were reproved according to the commercial, sanitary, and food safety quality indicators. Aspergillus, Cladosporium and Penicillium were the most common genera. Toxigenic evaluation showed that 25% of the A. flavus strains produced aflatoxins. The high rate of contamination of products bearing an inspection seal emphasizes the need to monitor the entire procedure of bee pollen production, as well as to revise the current legislation to ensure safe commercialization of this product.